Controlled Charging of Electrical Vehicles on Residential Power Grid - Hindér, Johan; Wijk, Simon (My University, 2018)
The market for electric vehicles (EVs) is growing explosively and shows no signs of stopping. With more and more owners of EVs, a significant load increase on the power grid is to be expected. EV owners in residential areas often share a connection to the power grid, where the maximum current is split evenly among a number of electric vehicle supply equipments (EVSEs) sharing the connection. If the EVSEs using this connection could have a common knowledge about how much power is available at the power grid connection and shared this among currently connected EVSEs the available power would seem higher than if the available current is shared equally among residents not using it for the moment. This thesis report covers an attempt to make an intelligent EVSE that can be installed at already existing charging lots in residential areas where the parking lots are located far apart. The EVSEs should use a wireless connection to remove the cost of laying new cables and enable easy installing. The report contains a comparison of new long-range communication technologies to find the best suited solution for the intelligent EVSE. The charging shall be controlled by a centralised server, from where charging can be enabled and disabled based on a schedule or human interaction. With this prototype system we hope to enable easy and low-cost installation of smart EV charging in residential areas.
Keywords: Informations- och kommunikationsteknik; Data- och informationsvetenskap; Information & Communication Technology; Computer and Information Science